Faculty of Electrical Engineering - Jan Michalik (Communications, 2003)
The Faculty of Electrical Engineering was founded in 1953 as one of three faculties of the Railway College in Prague, and was re-established during restructuralization changes in 1992. At present the process of faculty development still continues and some new branches of educational, research and technological development complete the traditional educational orientations, namely: information technologies, power electronic systems and modern methods of electric networks control. The interdisciplinary branches as for example mechatronics, telecommunication management and biomedicine are also in progress.